Peranan Sekolah Untuk Meningkatkan Civic Education Berdasarkan Nilai Pancasila Pada SMA Di Kecamatan Idi Rayeuk - Aiyub, Muhammad; Hasanah, Hasanah; Winarty, Asih; Tamarli, Tamarli; Jamal, Suwardi (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2025)
Civic education serves as a strategic means to instill national and state awareness, particularly among the youth who will become the nation's future leaders. The situation at SMA Negeri 1 in Idi Rayeuk sub-district shows that the implementation of Pancasila values in civic education learning is still not optimal, marked by monotonous learning methods, low motivation and student engagement, and a dominance of cognitive aspects in civic education that overlooks the formation of attitudes and character. The aim of this research is to understand the implementation of civic education among students and to know the role of schools in instilling civic education values through civic education learning. This research uses a descriptive method with a qualitative approach. The data collection techniques used are interviews, observations, and documentation. The research results show that: 1) The implementation of civic education at SMA Negeri 1 Idi Rayeuk is still not fully It aims to realize the ideal goals as a means of fostering the character of citizens who are aware, critical, and responsible. Students are still experiencing learning that is memorization-based, less contextual, and minimal in active participation. 2) The role of schools in instilling civic education values through PPKn learning at SMA Negeri 1 Idi Rayeuk still faces various complex challenges, both from the pedagogical approach, school culture, facility support, to policy consistency. Schools have not yet fully become a space that is democratic, participatory, and inclusive, which can serve as a living example for students in fulfilling their roles as citizens.ABSTRAKCivic education menjadi sarana strategis untuk menanamkan kesadaran berbangsa dan bernegara, khususnya di kalangan generasi muda yang akan menjadi penerus kepemimpinan bangsa. Kondisi yang terjadi di SMA Negeri 1 di Kecamatan Idi Rayeuk menunjukkan bahwa implementasi nilai-nilai Pancasila dalam pembelajaran civic education masih belum optimal, ditandai dengan metode pembelajaran yang monoton, rendahnya motivasi serta keaktifan siswa, dan dominasi aspek kognitif dalam pembelajaran PKN yang mengabaikan pembentukan sikap dan karakter. Tujuan penelitian ini adalah untuk mengethaui Implementasi civic education pada Siswa dan mengetahui Peranan sekolah dalam menanamkan nilai-nilai civic education melalui Pembelajaran PKN. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan dokumentasi.  Hasil penelitian menunjukkan bahwa: 1) Implementasi Civic Education di SMA Negeri 1 Idi Rayeuk masih belum sepenuhnya mampu mewujudkan tujuan ideal sebagai sarana pembentukan karakter warga negara yang sadar, kritis, dan bertanggung jawab. Siswa masih mengalami pembelajaran yang bersifat hafalan, kurang kontekstual, dan minim partisipasi aktif. 2) Peranan sekolah dalam menanamkan nilai-nilai civic education melalui pembelajaran PPKn di SMA Negeri 1 Idi Rayeuk masih menghadapi berbagai tantangan yang kompleks, baik dari sisi pendekatan pedagogik, kultur sekolah, dukungan fasilitas, hingga konsistensi kebijakan. Sekolah belum sepenuhnya menjadi ruang yang demokratis, partisipatif, dan inklusif, yang mampu menjadi teladan hidup bagi siswa dalam menjalani peran sebagai warga negara.